(untitled) (Advances in Military Technology, 2022)
The article deals with one of possible approaches how to create the alternate model of pilot behaviour in the process of aircraft flight control, especially in the situation when a repression of fast high oscillations of aircraft is eligible. Therefore the analysis and simulation of man behaviour with respect to automatic regulation view is introduced. Results of simulation of his response to the input pulse, and results of integration man-pilot to the circuit of absorbing high oscillations, are also presented.